Analysis of Remedial and Enrichment of Mathematics Teaching in a Junior High School in Bandung - Andini, Meri; Prabawanto, S (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Remedial and enrichment are processes that must be carried out by teacher based on the results of the assessment (as, of, and for learning). The importance of remedial and enrichment is to help and facilitate all the needs of students including achieving mastery learning and maximizing students's competency. This study aims to analyze remedial and enrichment processes carried out by mathematics teacher in a junior high school in Bandung. The method of this study was qualitative with descriptive approach. The data were collected by using observation, interview, and literature review. The subject of this study was a seven grade teacher of a junior high school. The result of the study shows that the teacher conducts remedial and enrichment conditionally. Remedial techniques used by the teacher are giving assignments, and/or giving remedial teaching. Furthermore, enrichment technique used by teacher is giving non-routine tasks for students. The implementation of the remedial and enrichment is not consistent for each event (daily assessment) because of some constraints, such as availability of time. Besides that, the teacher applies same strategy as before (not in remedial and enrichment)